Políticas de turismo e sustentabilidade em comunidades tradicionais: perspectivas conceituais - PINTO, Paulo Moreira (Universidade Federal do Pará, 2017)
The public policies of tourism in Brazil and in the Amazon, analyzing its implications in the political and administrative reality of traditional communities and its relationship with the historical sustainability of those populations in relation to the natural environment. It is an exploratory research, and in order to achieve its goal, describes the trajectory of the public policies of tourism in Brazil and, particularly, in the Amazon confronting them with theoretical background that support the formation of public policies, specially of sustainable tourism, which permeates the new programs of tourism and foresees the inclusion of community participation as an important element to carry out the public policies of tourism.